2021
DOI: 10.1097/mca.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of neutrophil-to-lymphocyte ratio across all stages of coronary artery disease

Abstract: The natural history of coronary heart disease (CAD) commonly begins with atherosclerosis, progressing to chronic coronary syndrome (CCS), acute coronary syndrome (ACS), and eventually, heart failure. Despite advancements in preventive and therapeutic strategies, there is room for further cardiovascular risk reduction. Recently, inflammation has emerged as a potential therapeutic target. The neutrophil-to-lymphocyte ratio (NLR) is a novel inflammatory biomarker which predicts poor prognosis in several condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 78 publications
1
32
0
Order By: Relevance
“…Recently, Agarwal et al (25) reviewed the prognostic value of NLR across all stages of CHD. In the review of Agarwal, three studies (26-28) reported that higher NLR was associated with increased risk of all-cause death or cardiac death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Agarwal et al (25) reviewed the prognostic value of NLR across all stages of CHD. In the review of Agarwal, three studies (26-28) reported that higher NLR was associated with increased risk of all-cause death or cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanistic pathways may connect NLR to adverse prognosis in CHD patients. First, previous studies (25,31)suggested that increased neutrophils can result in the production of vascular endothelial growth factor (VEGF), IL-1, IL-6, and IL-17, which all were reported to be associated with adverse outcomes of CHD. Second, lymphocytes have been suggested to play a role in the modulation of the inflammatory response throughout the atherosclerotic process (32).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated whether laboratory parameters of complete blood count or biochemical analysis could predict ISR, but yielded inconsistent results (6)(7)(8)(9)(10)(11)(12). Moreover, previous studies only employed bare-metal stent (BMS) and blood samples from the peri-interventional period and did not supplement with a dynamic follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil to lymphocyte ratio (NLR) is a simple marker of inflammatory reactions activation and has been postulated to play a clinical role as a predictive marker in oncology and cardiology [ 5 , 6 , 7 , 8 , 9 ]. The relationship between low values of NLR and rejection episodes in corneal transplantation has already been presented [ 10 ].…”
Section: Introductionmentioning
confidence: 99%